Implementasi Manajemen Kinerja Pegawai Pada Dinas Perpustakaan Dan Kearsipan Kota Yogyakarta - Fitriyuliani (Journal of Society Bridge, 2024)
Performance management begins with planning, requiring inputs that are processed to produce outputs beneficial to the organization. Evaluation involves systematic analysis, assessment, problem identification, and proposing alternative solutions. This is essential to ensure optimal public service, making the quality of civil servants' performance a key factor in national progress. This study examines the implementation of performance management for employees at the Yogyakarta City Library and Archives Office using a qualitative approach. Purposive sampling was applied to 11 civil servants, with data collected through interviews, observations, and document studies. The results show that employee performance management is well-implemented, supported by effective communication, resources, disposition, and bureaucratic structure.